French travelers in Andalusia (Siglo XIX): Stories and representations (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2021)
Travel literature is a genre well known for historiography, in which travels have been analyzed from the Antiquity to Contemporaneity. Traditionally, however, it’s travel literature produced by male travellers that had got a particular interest, while travel literature from female travellers has been treated to a lesser extent. This fact has been corrected in recent times thanks to the work of some researchers who have analysed and made visible female authors of travel stories. In this work, we propose to make known a series of female travellers, some of them very well known, but others practically unknown, all of them intrepid and daring women, who travelled through Spain (19th century-early 20th century). This will allow us to get closer to their biographies, their literary and professional careers and their stories about Spain.
Keywords: women; travellers; women's literature; travel literature; travellers-writers